2022
DOI: 10.3390/ijerph191811186
|View full text |Cite
|
Sign up to set email alerts
|

Association between Short-Term Exposure to Ozone and Heart Rate Variability: A Systematic Review and Meta-Analysis

Abstract: At present, ambient air pollution poses a significant threat to patients with cardiovascular disease (CVD). The heart rate variability (HRV) is a marker of the cardiac autonomic nervous system, and it is related to air pollution and cardiovascular disease. There is, however, considerable disagreement in the literature regarding the association between ozone (O3) and HRV. To further investigate the effects of short-term exposure to O3 on HRV, we conducted the first meta-analysis of relevant studies. The percent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 55 publications
(83 reference statements)
0
2
0
Order By: Relevance
“…Populations in Northern China were found to have a significantly higher risk of mortality due to cardiovascular disease related to ozone exposure, as reported in our study ( 19 ). Furthermore, several meta-analyses have reported a positive association between short-term exposure to ozone and cardiovascular diseases ( 20 , 21 ).…”
Section: Discussionmentioning
confidence: 99%
“…Populations in Northern China were found to have a significantly higher risk of mortality due to cardiovascular disease related to ozone exposure, as reported in our study ( 19 ). Furthermore, several meta-analyses have reported a positive association between short-term exposure to ozone and cardiovascular diseases ( 20 , 21 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, the potential for residual confounding by traffic remains due to the imperfect correlation between NO 2 and TRAP.. In terms of adjusting for O 3 and as observed by a recent systematic review, it is important to consider adjustment for O 3 since an association has been observed between short-term exposure to O 3 and a decrease in HRV ( 51 ). Moreover, in a study conducted on HRV in a two-pollutant model including PM 2.5 and O 3 , it was concluded that PM 2.5 influenced HRV rather than O 3 ( 31 ).…”
Section: Discussionmentioning
confidence: 99%